Financing Patterns Around the World : Are Small Firms Different? - Beck, Thorsten; Demirguc-Kunt, Asli; Maksimovic, Vojislav (2012)
Using a firm-level survey database covering 48 countries, we investigate how financial and institutional development affects financing of large and small firms. Our database is not limited to large firms but includes small and medium-size firms and data on a broad spectrum of financing sources, including leasing, supplier, development, and informal finance. Small firms and firms in countries with poor institutions use less external finance, especially bank finance. Protection of property rights increases external financing of small firms significantly more than of large firms, mainly due to its effect on bank finance. Small firms do not use disproportionately more leasing or trade finance compared with larger firms, so these financing sources do not compensate for lower access to bank financing of small firms. We also find that larger firms more easily expand external financing when they are constrained than small firms. Finally, we find suggestive evidence that the pecking order holds across countries.